PENERAPAN PROBLEM BASED LEARNING UNTUK HIGHER ORDER THINKING SKILLS PADA SISWA PENDIDIKAN TEKNIK INFORMATIKA - Dewanto, Satriyo Agung; Marpanaji, Eko; Mahali, Muh. Izzudin; Hasanah, Nur; Wulandari, Bekti (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2018)
This research has purpose to know the difference between student learning result with computer network practice course and higher order thinking skill (HOTS) given by demonstration method with problem based learning (PBL) method. This research is a research using quasi experiment consisting of two classes as sample. The one class uses the demonstration learning method, while the other class uses the PBL method. This study has an analysis using t-test. the result of this research is able to show there is difference between student learning outcomes with high thinking ability in computer network practice class among students given demonstration method with students given PBL method. Students who were given demonstration learning methods resulted less than students who had been provided with PBL methods in order to improve learning outcomes.